2019
DOI: 10.1002/tox.22840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenanthrene on oxidative stress and inflammation in lung and liver of female rats

Abstract: Phenanthrene (Phe) female rat model was established to explore the effects of Phe on oxidative stress and inflammation. The rats were randomly divided into three groups including control (C), low (L), and high (H) group. Phe was supplied to L and H groups at the dosage of 180 mg/kg and 900 mg/kg orally at first day, and with the dose 90 mg/kg and 450 mg/kg by intraperitoneal injection at the last 2 days. The C group was enriched with the same volume of corn oil. The blood, lung, and liver tissues were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 45 publications
6
22
0
Order By: Relevance
“…Our early population study found that rural women exposed to PAHs in the winter were significantly associated with the oxidative damage and repression of immune functions. 26 And our animal model of acute toxicity revealed that Phe could increase SOD activity and MDA content in female rats, 16 which indicating the occur- and CAT, as critical antioxidant enzymes, were both triggered clearly to protect against superoxide radicals, as reported elsewhere. 10,29,30 And the results could make up and verify our previous studies on oxidative damage in some way.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Our early population study found that rural women exposed to PAHs in the winter were significantly associated with the oxidative damage and repression of immune functions. 26 And our animal model of acute toxicity revealed that Phe could increase SOD activity and MDA content in female rats, 16 which indicating the occur- and CAT, as critical antioxidant enzymes, were both triggered clearly to protect against superoxide radicals, as reported elsewhere. 10,29,30 And the results could make up and verify our previous studies on oxidative damage in some way.…”
Section: Discussionsupporting
confidence: 79%
“…34 Our previous population investigation confirmed that PAHs exposure could impair immune functions of rural women by changing the cytokines related to inflammation, and our later animal experiments found that Phe could lead to oxidative stress and inflammation in female rats. 16,26 This study also demonstrated that Phe, Flu, and their mixture could not only induce oxidative damage in A549 cells but also inflammatory response and other related pulmonary effects. Phe, Flu, and their mixture were exposed to all tested concentrations to assess the dose-effect relationship of the inflammatory response.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations